ON THE NEW RECORD OF Lithoselatium kusu Schubart, Liu and Ng, 2009 FROM INDONESIA (CRUSTACEA: BRACHYURA: SESARMIDAE) - Widyastuti, Ernawati; Rahayu, Dwi Listyo (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
Lithoselatium kusu Schubart, Liu and Ng, 2009 previously known from Singapore and surrounding areas, in this paper reported for the first time from Indonesia. The specimens for this study were collected from under rocks and coral rubble around mangrove areas in Lingga, Indonesia. The morphological characteristics and differences of the three known species of this genus are presented.